Community Social Confflict and Production Suction Vessels (KIP) in matras Waters, Sungailiat District, Bangka Regency - Ronaldy Escobar (Inovbook Publications, 2022)
This study aims to obtain information, to what extent the Community Social Conflict and Production Suction Vessels (KIP) in Matras Waters, Sungailiat. The phenomenon of social conflict that occurs in the community due to mining activities, especially Tin mining in Bangka Belitung, is increasingly happening and is in the spotlight of various media, especially what is happening in the Sungailiat Mat waters, where social conflict problems arise due to marine tin mining activities carried out by Suction Ships. Production (KIP) causes various problems, namely conflicts that occur in the Matras community. As is known, Matras waters are one of the fishing areas for people who work as traditional fishermen, and Matras waters are also one of the mainstay tourist destinations in Sungailiat, so it is very unfortunate if the existing marine ecosystem is damaged as a result of the sea tin mining activities carried out by this Production Suction Vessel, and the damaged marine ecosystem will have a profound impact on life. Matras community whose economic source depends on existing marine products. Based on the results of initial observations, researchers are interested in researching the problem of Social Conflict that occurs related to the existence of Sea Tin mining activities carried out by Production Suction Vessels in the Matras waters. The purpose of this study is to find out how the dynamics of conflicts that arise related to the problems of operating the Production Suction Vessel in the Matras waters. This research uses conflict theory from Ralf Dahendorf which assumes that the first task to analyze conflict is to identify various roles of authority, and differences in interests between groups that affect conflict can occur, so researchers use conflict theory from Ralf Dahendorf to see the dynamics of conflicts that occur related to the operation Production Suction Vessel (KIP) in Matras waters. The method used in this research is qualitative using a case study approach which intends to describe the results of the study and try to find a comprehensive picture of a situation, and the data collection techniques used are interviews, observation, documentation. Sources of data used in the study came from primary and secondary data, and analyzed through 3 stages, namely data reduction, data display, and drawing conclusions. The findings in this study indicate that there are 4 stages of conflict dynamics that occur related to the operation of the Production Suction Vessel in the Mats waters, namely, the first pre-conflict stage, the second confrontation stage, the third crisis stage/conflict peak, and the fourth post-conflict stage.